Postpartum Haemorrhage Occurrence Seen from Influencing Factors - Titin Susiyanti; Byba Melda Suhita; Nurdina Nurdina (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2019)
The biggest cause of maternal mortality rates in developing countries, one of which is bleeding after childbirth or commonly called postpartum hemorrhage (PPP). This study was conducted to determine factors that influence the incidence of postpartum hemorrhage. Observational research design with a case control approach. held on 1 - 31 August 2018 with a population of 109 people and a sample of 90 mothers giving birth, sample random sampling technique. Data collection is independent and dependent variable by observation and questionnaire. Data analysis uses logistic regression test. Based on the results of logistic regression test obtained variable bleeding history postpartum p value value of 0.019, preeclampsia p value of 0.012, anemia p value of 0.009 at α = 0.05, the effect of the incidence of postpartum hemorrhage was influenced by a history of postpartum hemorrhage, preeclampsia and anemia significantly. Anemia is a dominant risk factor contributing to the incidence of postpartum hemorrhage. It is recommended that pregnant women take precautions as early as possible with regular pregnancy checks, knowing the factors preventing the occurrence of postpartum hemorrhage, be more careful to prevent complications at the time of delivery.